Lutzomyia longipalpis Saliva Drives Interleukin-17-Induced Neutrophil Recruitment Favoring Leishmania infantum Infection - Teixeira, Clarissa R.; Santos, Claire da S.; Prates, Deboraci B.; dos Santos, Rafael T.; Araújo-Santos, Théo; de Souza-Neto, Sebastião M.; Borges, Valéria M.; Barral-Netto, Manoel; Brodskyn, Cláudia I. (Frontiers in Microbiology, 2018)
During bloodfeeding, the presence of sand fly saliva in the hemorrhagic pool where Leishmania is also inoculated modulates the development of host immune mechanisms creating a favorable environment for disease progression. To date, information obtained through experimental models suggests that sand fly saliva induces cellular recruitment and modulates production of eicosanoids. However, the effect of sand fly saliva in the different steps of the inflammatory response triggered by Leishmania remains undefined. Here we further investigate if interaction of Lutzomyia longipalpis salivary gland sonicate (SGS) with different host cells present during the initial inflammatory events regulate Leishmania infantum infectivity. Initially, we observed that incubation of human peripheral blood mononuclear cells (PBMC) with Lu. longipalpis SGS in the presence of L. infantum significantly increased IL-10 but did not alter expression of IFN-γ and TNF-α by CD4+ T cells induced by the parasite alone. Interestingly, incubation of PBMC with Lu. longipalpis SGS alone or in the presence of L. infantum resulted in increased IL-17 production. The presence of IL-17 is related to neutrophil recruitment and plays an important role at the site of infection. Here, we also observed increased migration of neutrophil using an in vitro chemotactic assay following incubation with supernatants from PBMC stimulated with L. infantum and Lu. longipalpis SGS. Neutrophil migration was abrogated following neutralization of IL-17 with specific antibodies. Moreover, culture of human neutrophils with L. infantum in the presence of Lu. longipalpis SGS promoted neutrophil apoptosis resulting in increased parasite viability. Neutrophils operate as the first line of defense in the early stages of infection and later interact with different cells, such as macrophages. The crosstalk between neutrophils and macrophages is critical to determine the type of specific immune response that will develop. Here, we observed that co-culture of human macrophages with autologous neutrophils previously infected in the presence of Lu. longipalpis SGS resulted in a higher infection rate, accompanied by increased production of TGF-β and PGE2. Our results provide new insight into the contribution of Lu. longipalpis SGS to L. infantum-induced regulation of important inflammatory events, creating a favorable environment for parasite survival inside different host cells.